PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI INSTAGRAM (Studi Kasus Pada Mahasiswa Universitas Teknologi Sumbawa Angkatan Tahun 2016 Sampai Dengan Tahun 2018) - Citra Ardianti; Abdul Salam; Hanifa Sri Nuryani (Journal of Management and Business, 2020)
This study aims to examine the effects of: 1) The influence of celebrity endorsers on purchasing decisions. 2) The influence of brand image on purchasing decisions. 3) The influence of celebrity endorser and brand image on purchasing decisions. The model used in data analysis is instrument test, classic assumption test, multiple linear regression analysis and hypothesis testing. The analytical tool used in this study was SPSS 16. The data used were primary data with a purposive sampling technique. The results of this study indicate that: 1) Celebrity endorser has a significant effect on purchasing decisions with a tcount of 2.791 greater than ttable, namely 1.984 with a significance value of 0.003 less than 0.05. 2) Brand image has a significant effect on purchasing decisions with a t-count value of 10,800 greater than t-table, namely 1.984 with a significance value of 0.000, less than 0.05. 3) Celebrity endorser and brand image simultaneously have a significant effect on purchasing decisions with a value of Fcount of 89.950 greater than Ftable, which is 3.09 with a significance value of 0.000 less than 0.05.